ACUTE TOXICITY OF COPPER, ZINC AND MERCURY ON INTERTIDAL GASTROPODS OF MUMBAI COAST - Jaiswar, A. K.; Kulkarni, B. G.; Thakur, M. K. (Journal of Indian Fisheries Association, 2015)
The acute toxicity test conducted by static bioassay techniques haverevealed that among selected heavy metals, copper is more toxic than zincand mercury to Planaxis sulcatus and Trochus radiatus. The naturalavailability of heavy metals in the surrounding environment of theseorganisms is found to be deciding factor for their toxicity. Natural habitatof the animal also contributes to the sensitivity of a particular animal to theheavy metals tested. In addition the tendency of the animal to overcome theadverse conditions in their surrounding also plays a significant role in toxicityof pollutants.Keywords: Intertidal, Nerita oryzarum, Planaxis sulcatus, Trochus radiatus,Copper, Zinc, Mercury